Digital Flipbook Comics with A Mindfulness-Cognitive Behavioral Harmony Approach - Ni Kadek Putri Ayu Dwiadiningsih; I Nyoman Jampel; Kadek Yudiana (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2026)
Elementary school students' learning comfort is often hampered by learning approaches that are less adaptive to children's emotional and cognitive needs. The low level of student involvement in mathematics learning in class V is the background for the need for innovative learning media that not only convey material but also support students' psychological well-being. This research aims to develop flipbook-based digital comic media using a mindfulness-cognitive-behavioral harmony approach to enhance students' comfort in learning. This research uses the research and development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation and evaluation. The subjects comprised material experts, media experts, class teachers, and 32 Class V students. Data were collected through validation questionnaires, practicality tests, and learning comfort tests, and analyzed using a paired-samples t-test. The results show that the media is in the very valid category (material validation score 0.88 and media 0.92), very practical (teacher practicality score 3.97 and students 3.62), and effective in increasing learning comfort (significance value 0.000 less 0.05). These findings confirm that integrating emotional and cognitive aspects into learning media can create a more comfortable learning experience. The practical implication is that this medium has the potential to be an alternative solution for designing learning that is based on student welfare at the elementary school level.